Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd005261.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment for ruptured abdominal aortic aneurysm

Abstract: New search run. One new study included. No new studies excluded. Text updated to reflect current Cochrane standards. 'Summary of findings' table added. No change to conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 57 publications
1
29
0
1
Order By: Relevance
“…45 ). This study, another prospective randomized studies (AJAX, IMPROVE) and meta-analysis showed no difference in perioperative mortality [45][46][47][48][49] . Perioperative mortality is 20-50% (ref.…”
Section: Treatment Of Ruptured Aneurysmssupporting
confidence: 50%
See 1 more Smart Citation
“…45 ). This study, another prospective randomized studies (AJAX, IMPROVE) and meta-analysis showed no difference in perioperative mortality [45][46][47][48][49] . Perioperative mortality is 20-50% (ref.…”
Section: Treatment Of Ruptured Aneurysmssupporting
confidence: 50%
“…Perioperative mortality is 20-50% (ref. 48,49 ). The results of above mentioned studies AJAX and IMPROVE have recently been questioned on methodological errors and it is stated that the results of endovascular treatment of RAAA could have been better compared with surgical repair.…”
Section: Treatment Of Ruptured Aneurysmsmentioning
confidence: 99%
“…Post hoc analysis of REDOXS data suggested that the presence of multi-organ failure that included renal dysfunction at study entry was most strongly associated with the mortality signal with GLN administration (51). However, the current GLND trial differs from the REDOX trial in that it was conducted exclusively in post-operative SICU patients, excluded those in shock or with significant renal/hepatic dysfunction at entry, and provided a lower, more conventional GLN dose (50, 52), in conjunction with complete PN ± EN support, with GLN-PN started several days after ICU admission in resuscitated patients. Given several decades of published RCTs and numerous meta-analyses suggesting the clinical and metabolic benefits of GLN-supplemented PN (612, 1620, 3236), it remains unclear why we were unable to observe a signal of benefit in this or recent RCTs of GLN-supplemented PN (2425).…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted in Europe did not reveal significant difference between EVAR and OAR used for the treatment of ruptured AAA in the shortterm outcomes (31,33,35). Moreover, for the patients undergoing elective operations of AAA and emergency procedure for the ruptured AAA relatively low rate of perioperative mortality and well long-term survival were reported for both methods of treatment (31,33,35,42,43,45). In view of technical difficulties in videoscopic approach with a long learning curve and high cost of robotic system, EVAR or OAR remain routine methods used for AAA repair in the world.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Badger at al. no relevant advantages in shortterm outcomes for endovascular repair of the ruptured AAA were revealed and the perioperative mortality was comparable for the both methods, with odds ratio 0.91 (95% confidence interval 0.67 to 1.22, p = 0.52) (33). In the study conducted in the Netherlands, the investigators evaluated the same parameters in the patients with the ruptured AAA but the analysis included also long-term outcomes.…”
Section: In Europementioning
confidence: 99%